Taxonomic relevance of leaf surface micromorphology in Korean Clematis L. (Ranunculaceae) - Ghimire, Balkrishna; Park, Beom Kyun; Son, Dong Chan (PeerJ, 2024)
Clematis, one of the largest genera of the family Ranunculaceae, has a wide array of morphological variation and is considered the most difficult group of taxa in terms of infrageneric discrimination. This study assessed the leaf micromorphological features of 19 Clematis taxa (16 species and three varieties) found in Korea. The leaf surface features were studied under scanning electron microscopy, and the stomatal counting and measurement were carried out under light microscopy. Clematis are hypostomatic, meaning the stomata are only found on the abaxial surface of the leaf. Observed taxa showed near uniformity in the epidermal cell type, structure, and morphology on both surfaces of the leaf. Differences were observed in the presence and absence and/or abundance of trichomes on both the adaxial and abaxial surfaces, the epidermal cell boundary, and the periclinal and anticlinal wall of the cells. Differences were also observed in the number of the epidermal cells connected with the stomata on the abaxial surface, with small differences noted in epidermal cell shapes. The ANOVA showed a significant variation in the stomata density in the studied taxa (P < 0.0001). The cluster analysis based on 13 leaf micromorphological features generated four major clusters. These results indicated similarities in certain key leaf micromorphological features among taxa from the Tubulosae, Clematis, and Virona sections. In the genus Clematis, as with other morphological characteristics, using leaf micromorphological characters alone, which possess limited taxonomic value, proves inadequate for resolving infrageneric relationships. However, incorporating certain features with other morphological characteristics offers a possible alternative means of determining the infrageneric relationships within the genus.
Keywords: Clematis; Leaf micro-morphology; Stomata; Trichomes; Taxonomic discrimination